Answer:
0.85
Step-by-step explanation:
Answer:
Step-by-step explanation:
Answer:
87
Step-by-step explanation:
sorry if im wrong
<span>If y varies directly with x, the formula of the equation is y=ax, where a is a constant.
y=ax
(21)=a(7)
a=3
y=ax
y=(3)(-1.66)
y=-4.98, x=-1.66
If y varies inversely with x, the formula of the equation is y=a/x, where a is a constant
y=a/x
9=a/2.5
a=22.5
y=22.5/x
y=22.5/-0.6
y=-37.5
I hope this helped! =)
I hope you didn't mind but I got this from a website called: answers.yahoo.com but I got your answer.
</span>
Answer:
<h2>(2x^2+5x-3)-(x^2+x-6)</h2>
Step-by-step explanation:
That is the only one I could find. It is a simple matter of simplifying each equation and seeing if it will match the given: x^2+4x+3. Make sure that you properly distribute and watch your signs (-/+)